Perturbations of Multipliers of Systems of Periodic Ordinary Differential Equations (Advances in Applied Mathematics and Mechanics, 2011)
The paper deals with periodic systems of ordinary differential equations (ODEs).A new approach to the investigation of variations of multipliers underperturbations is suggested. It enables us to establish explicit conditions for the stability and instability of perturbed systems.